2017
DOI: 10.1016/s1473-3099(17)30242-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of a parenteral P2-VP8-P[8] subunit rotavirus vaccine in toddlers and infants in South Africa: a randomised, double-blind, placebo-controlled trial

Abstract: Bill & Melinda Gates Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
135
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(136 citation statements)
references
References 28 publications
1
135
0
Order By: Relevance
“…A combination of oral and parenteral vaccines (inactivated or recombinant non-live vaccines) or only parenteral vaccines might be useful in this regard 90 . Indeed, a parenterally administered recombinant VP8* vaccine is safe and immunogenic in children 131 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…A combination of oral and parenteral vaccines (inactivated or recombinant non-live vaccines) or only parenteral vaccines might be useful in this regard 90 . Indeed, a parenterally administered recombinant VP8* vaccine is safe and immunogenic in children 131 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…28 Results of four more phase I trials in the United States and Canada were reported simultaneously (Regules et al, NEJM 2016) or shortly thereafter. [29][30][31] To date, a total of 17 phase I-III clinical trials have been completed or are ongoing (summarized in Tables 1 and 2). 16,32 VSV-EBOV is furthermore the only vaccine that is being deployed during the 10 th EBOV outbreak in the Democratic Republic of the Congo (DRC).…”
Section: Ebola Virusmentioning
confidence: 99%
“…After the study halt, simultaneously running phase I studies of VSV-EBOV included arthralgia/arthritis as a solicited adverse event, but while transient arthralgia was likewise reported, the high frequency of arthritis cases was not observed to the same extent. [28][29][30][31]41 Finally, arthritis frequency was assessed in a large placebocontrolled phase III trial. Here, the incidence of arthritis or joint swelling was 4.9% in a study population of 1050 individuals.…”
Section: Safety Datamentioning
confidence: 99%
“…Two candidates are being developed: a trivalent nonreplicating rotavirus vaccine expressed in E. coli, developed by PATH -SK Bioscience as partner-showed good safety and immunogenicity (e.g. neutralizing antibodies) in human clinical studies [13], clinical protection will be evaluated. The inactivated whole-virus particle Rotavirus vaccine developed by the U.S. CDC -SII as partner -showed protective immunity in animals.…”
Section: Future Vaccinesmentioning
confidence: 99%